Characterization of the zinc finger μ-protein HVO_0758 from Haloferax volcanii: biological roles, zinc binding, and NMR solution structure - Üresin, Deniz; Pyper, Dennis J.; Borst, Andreas; Hadjeras, Lydia; Gelhausen, Rick; Backofen, Rolf; Sharma, Cynthia; Schwalbe, Harald; Soppa, Jörg (Frontiers in Microbiology, 2023)
It is increasingly recognized that very small proteins (µ-proteins) are ubiquitously found in all species of the three domains of life, and that they fulfill important functions. The halophilic archaeon Haloferax volcanii contains 282 µ-proteins of less than 70 amino acids. Notably, 43 of these contain two C(P)XCG motifs, suggesting their potential to complex a zinc ion. To explore the significance of these proteins, 16 genes encoding C(P)XCG proteins had been deleted, and the majority of mutants exhibited phenotypic differences to the wild-type. One such protein, HVO_2753, was thoroughly characterized in a previous study. In the present study an in-depth analysis of a second protein, HVO_0758, was performed. To achieve this goal, the HVO_0758 protein was produced heterologously in Escherichia coli and homologously in H. volcanii. The purified protein was characterized using various biochemical approaches and NMR spectroscopy. The findings demonstrated that HVO_0758 is indeed a bona fide zinc finger protein, and that all four cysteine residues are essential for folding. The NMR solution structure was solved, revealing that HVO_0758 is comprised of an N-terminal alpha helix containing several positively charged residues and a globular core with the zinc finger domain. The transcriptomes of the HVO_0758 deletion mutant and, for comparison, the HVO_2753 deletion mutant were analyzed with RNA-Seq and compared against that of the wild-type. In both mutants many motility and chemotaxis genes were down-regulated, in agreement to the phenotype of the deletion mutants, which had a swarming deficit. The two H. volcanii zinc-finger µ-proteins HVO_0758 and HVO_2753 showed many differences, which are subject to detailed discussion. Taken together, two zinc finger µ-proteins of H. volcanii have been characterized intensively, which emerged as pivotal contributors to swarming behavior and biofilm formation.